2018
DOI: 10.1186/s13148-018-0472-5
|View full text |Cite
|
Sign up to set email alerts
|

Placental surface area mediates the association between FGFR2 methylation in placenta and full-term low birth weight in girls

Abstract: BackgroundFibroblast growth factor receptor 2 (FGFR2) gene encodes a protein of the fibroblast growth factor receptor family. FGFR2 gene expression is associated with the regulation of implantation process of placenta which plays a vital role in fetal growth. DNA methylation is widely known as a mechanism of fetal growth. However, it is unclear whether and how DNA methylation of FGFR2 gene in the placenta is associated with full-term low birth weight. This case-control study aims to explore the links between F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…PAI-1 has been associated with a high pro-angiogenic activity at physiological concentrations [ 50 ], and its up- or downregulation promotes or inhibits blood vessel formation, respectively [ 51 , 52 ]. PAI-1 has been previously reported to be elevated in the serum of patients with GDM [ 43 ], and it is known to be upregulated by the pro-angiogenic placental growth factor gene [ 53 ]. In agreement with these data, we observed that TM5275, a PAI-1 selective pharmacological inhibitor, substantially attenuated the angiogenic capacity of GDM-hAMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 has been associated with a high pro-angiogenic activity at physiological concentrations [ 50 ], and its up- or downregulation promotes or inhibits blood vessel formation, respectively [ 51 , 52 ]. PAI-1 has been previously reported to be elevated in the serum of patients with GDM [ 43 ], and it is known to be upregulated by the pro-angiogenic placental growth factor gene [ 53 ]. In agreement with these data, we observed that TM5275, a PAI-1 selective pharmacological inhibitor, substantially attenuated the angiogenic capacity of GDM-hAMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal socio-demographic characteristics, medical and reproductive history were collected via clinic interviews after delivery, and pregnancy information (e.g., pregnancy complications, offspring biometric measures at birth) were extracted from medical records by trained study staff, the questionnaire used in the interviews had been employed in our previous works [3537]. Details of delivery were measured and recorded by midwives, including birth weight (measured to the nearest 5 g), birth length, head circumference, as well as placental diameters and thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation analysis showed that there was a positive correlation between FGFR2 CNVs and mRNA expression in pancancer (r = 0.1578, p < 0.0001) (Supplementary Figure 2B). In addition, some other factors might also affect the expression of FGFR2, such as methylation (43).…”
Section: Fgfr2 Cnvs In Different Cancer Typesmentioning
confidence: 99%